Regulation of Glutamate Dehydrogenases During Morphogenesis of Schizophyllum commune - Dennen, David W. (1967)
The specific activities of two glutamate dehydrogenases (GDH), one requiring nicotinamide adenine dinucleotide (NAD) and the other specific for nicotinamide adenine dinucleotide phosphate (NADP), varied during growth of Schizophyllum commune as a function of the stage of the life cycle and the exogenous nitrogen source. During basidiospore germination on either glucose-NH(3) or glucose-glutamate medium, NADP-GDH increased six- to eightfold in specific activity, whereas NAD-GDH was depressed. During dikaryotic mycelial growth on either nitrogen source, the two GDH increased in a 1:1 ratio, whereas, during homokaryotic mycelial growth on glucose-NH(3), NADP-GDH activity was depressed and NAD-GDH increased six- to eightfold. Homokaryotic mycelium cultured on glucose-glutamate medium yielded high NADP-GDH activities and normal NAD-GDH activities. Intracellular NH(3) concentration and NADP-GDH activities were inversely related during spore germination and homokaryotic mycelium growth, whereas guanosine-5′-triphosphate (GTP) and l-glutamine specifically inhibited NAD- and NADP-GDH respectively in vitro. GTP inhibition was shown in extracts from cells at all stages of the life cycle. Basidiospore germling extracts contained an NADP-GDH essentially resistant to l-glutamine inhibition.